Developing English Reading Comprehension Material Based On The SQ4R Technique For Class X In MAN 1 Mandailing Natal - Irmasari Irmasari; Ahmad Laut Hasibuan (Innovative: Journal Of Social Science Research, 2023)
This study aims to determine the development, validity and effectiveness of the development of English Reading Comprehension Material Based on The SQ4R Technique For Class X in MAN 1 MANDAILING NATAL This research is a research and development (R&D) using the Sugiyono model. The instrument used is a questionnaire for expert lecturers and students, interviews with teachers, and the results of the last test given to students. The test results from the validator through media design aspects of 100% in the very good category and 95,83% from material experts I and II in the very good category, so this product was declared worthy of being used as learning so that students were more active in participating in learning.And The effectiveness of the product can be known based on the results of student responses when using the product is very good. The results of student responses who answered "yes" were 84% and students who answered "no" were 16%. So the student response by answering "yes" is more than those who answered "no" so it can be criticised very well